2011
DOI: 10.5713/ajas.2011.11211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron Supplementation to Diets Deficient in Calcium and Phosphorus on Performance with Some Serum, Bone and Fecal Characteristics of Broiler Chickens

Abstract: Three levels of boron (0, 30, 60 ppm) were supplemented in practical corn-soybean based starter and grower diets, containing either adequate or inadequate Ca or P. A total of 1,800, 1-day-old sexed broiler chicks were assigned to six dietary treatments and fed with the experimental diets for 42 days. Boron improved the overall feed conversion ratio, but increased body weight only at 21 days of age (p<0.01). Boron decreased feed intake in the case of feeding on a diet deficient in Ca and P, and tended to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
(68 reference statements)
3
25
0
Order By: Relevance
“…Our results are in accord with several authors who reported no benefits in the bone ash and Ca concentration of broilers in response to boron supplementation of 20 to 150 mg/kg (Fassani et al, 2004;Çınar et al, 2015). However, others have reported significant increases in tibia Ca concentration (Armstrong et al, 2000;Kurtoğlu et al, 2005;Bozkurt et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accord with several authors who reported no benefits in the bone ash and Ca concentration of broilers in response to boron supplementation of 20 to 150 mg/kg (Fassani et al, 2004;Çınar et al, 2015). However, others have reported significant increases in tibia Ca concentration (Armstrong et al, 2000;Kurtoğlu et al, 2005;Bozkurt et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, a daily intake of 50 μg boron per day by humans via consumption of 200 g chicken breast meat should not result in toxic levels of boron. The combined evidence indicates that boron can interact with the metabolism of some macro-minerals, such as Ca, P and Mg, and ALP, thereby modifying their concentrations in the serum of broiler chickens (Kurtoğlu et al, 2001(Kurtoğlu et al, , 2005Bozkurt et al, 2012). However, here, the serum biochemical constituents were not affected by supplemental boron (P> 0.05).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Because of this reason, the physiological role of boron has been widely studied. Appropriate amount of boron has a beneficial effect on the growth and development of the bone [11][12][13][14][15], the proliferation and differentiation of blood cells [16], and the functions of the brain [17], while high-level boron was harmful [18,19]. However, to our knowledge, so far, no study has evaluated the effects of boron on brain development.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the serum P concentration was at its normal values except during calving in boron and control groups ( Table 2). We observed that serum P concentration was higher (P<0.05) in postpartum week 2 in group B than in group C. The data of the study on chickens show that boron supplementation to diets increased the serum P concentration (Kurtoğlu et al 2001, Bozkurt et al 2012, whereas another study on rabbits indicates that boron administration did not change the P concentration (Basoglu et al 2010).…”
Section: Resultsmentioning
confidence: 62%